Presumed Zika virus-related congenital brain malformations: the spectrum of CT and MRI findings in fetuses and newborns - José Daniel Vieira de Castro; Licia Pacheco Pereira; Daniel Aguiar Dias; Lindenberg Barbosa Aguiar; Joanira Costa Nogueira Maia; Jesus Irajacy Fernandes da Costa; Eveline Campos Monteiro de Castro; Francisco Edson de Lucena Feitosa; Francisco Herlânio Costa Carvalho (Arquivos de Neuro-Psiquiatria)
ABSTRACT The new epidemic of Zika virus infection raises grave concerns, especially with the increasingly-recognized link between emerging cases of microcephaly and this infectious disease. Besides small cranial dimensions, there are striking morphologic anomalies in the fetal brain. Key anomalies include cortical developmental malformations and a peculiar distribution of pathologic calcifications. These potentially indicate a new pattern of congenital central nervous system infection. Methods: Eight women underwent fetal MRI. Four infants also underwent postnatal CT. Five of the women underwent amniocentesis. Results: All neonates were born with microcephaly. On fetal MRI, ventriculomegaly, marked reduction of white matter thickness, severe sylvian fissure simplification, abnormal sulcation, and diffuse volumetric loss of cerebellar hemispheres were consistently seen. On postnatal CT, diffuse subcortical and basal ganglia calcifications were observed. The Zika virus was detected in two amniocenteses by polymerase chain reaction assays. Conclusion: We hope to assist the medical community in recognizing the spectrum of encephalic changes related to congenital Zika virus infection.